Sonic engagement : the ethics and aesthetics of community engaged audio practice - Woodland, Sarah; Vachon, Wolfgang (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"Sonic Engagement examines the relationship between community engaged participatory arts and the cultural turn towards audio, sound, and listening that has been referred to as the "sonic turn." This edited collection investigates the use of sound and audio production in community engaged participatory arts practice and research. The popularity of podcast and audio drama, combined with the accessibility and portability of affordable field recording and home studio equipment, makes audio a compelling mode of participatory creative practice. This book maps existing projects occurring globally through a series of case study chapters that exemplify community engaged creative audio practice. The studies focus on audio and sound-based arts practices that are undertaken by artists and arts-led researchers in collaboration with (and from within) communities and groups. These practices include - Applied audio drama, community-engaged podcasting, sound and verbatim theatre, participatory sound art, community-led acoustic ecology, sound and media walks, digital storytelling, oral history and reminiscence, and radio drama in health and community development. The contributors interrogate the practical, political, and aesthetic potentialities of using sound and audio in community engaged arts practice, as well as its tensions and possibilities as an arts-led participatory research methodology. This book provides the first extensive analysis of what sound and audio brings to participatory interdisciplinary arts-led research and practice, representing a vital resource for community arts, performance practice, and research in the digital age"--
Introduction: Distilling an Interdisciplinary Approach -- Part 1. First Knowledges First -- Part 2. Sonic Knowing: Meaning and Resonance -- Part 3. Sonic Assembly: Building Communities and Publics -- Part 4. Sonic Disruptions: Creating Auditory Counter-Narratives -- Part 5. Sonic Resistance: Soundscapes of Protest and Activism -- Concluding Acknowledgement.
Keywords: Performing arts -- Social aspects; Music -- Social aspects; Sound -- Social aspects; Community arts projects; PERFORMING ARTS / General; COMPUTERS / Data Processing / Speech & Audio Processing